2019
DOI: 10.3390/ani9110997
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Milk Fatty Acids in Holstein Cattle Accounting for the DGAT1 Gene Effect

Abstract: Simple SummaryMilk fat content and fatty acid composition are key traits for the dairy industry, as they directly influence consumer acceptance of dairy products and are associated with the chemical-physical characteristics of milk. In order to genetically improve milk fat composition, it is important to understand the biological mechanisms behind the phenotypic variability observed in these traits. In this study, we used a genomic dataset for 6692 animals and over 770,000 genetic markers distributed across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Important contributions were found on BTA14. This chromosome is well known to have a substantial number of QTL for milk and fat production traits (Viitala et al, 2003;Wang et al, 2013), including DGAT1, a gene involved in the last step of the synthesis of triacylglycerol and that has a major effect on milk fat content (Grisart, 2002;Cruz et al, 2019). Despite its importance, DGAT1 was not found in this study because of the absence of markers located in its proximity.…”
Section: Gwas and Functional Analysesmentioning
confidence: 72%
See 1 more Smart Citation
“…Important contributions were found on BTA14. This chromosome is well known to have a substantial number of QTL for milk and fat production traits (Viitala et al, 2003;Wang et al, 2013), including DGAT1, a gene involved in the last step of the synthesis of triacylglycerol and that has a major effect on milk fat content (Grisart, 2002;Cruz et al, 2019). Despite its importance, DGAT1 was not found in this study because of the absence of markers located in its proximity.…”
Section: Gwas and Functional Analysesmentioning
confidence: 72%
“…However, the peak observed at the beginning of BTA14 is likely in high linkage disequilibrium with markers located in DGAT1. In fact, conducting a GWAS for milk FA in the same population, Cruz et al (2019) identified DGAT1 when using the previous reference genome.…”
Section: Gwas and Functional Analysesmentioning
confidence: 99%
“…It was described that the FA synthesized de novo have moderate to high heritability estimates, while those transferred from blood are characterized by low to moderate heritability estimates as their content depends also on non-genetic factors such as feeding [8]. Moreover, fatty acids present high variability mostly because of the DGAT1 gene [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, genetic variations that affect human milk fat content were not reported to date. In contrast, owing to the high economic importance of fat contents in dairy products, this topic was characterized in depth in dairy animals [12,[89][90][91][92][93][94][95]. The diacylglycerol o-acyltransferase 1 (DGAT1) gene encodes for one of the enzymes that covalently attaches diacylglycerol to long-chain fatty acyl-CoAs to form triglycerides [96], which are the major fat type present in milk.…”
Section: Fat Percentage In Human Milkmentioning
confidence: 99%